2016
DOI: 10.1080/21645515.2016.1193658
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial L-forms are found in cord blood: A potential vertical transmission of BCG from vaccinated mothers

Abstract: Our previous studies showed that mycobacterial L-forms persist in the blood of BCG vaccinated people and that BCG vaccine is able to produce, under appropriate conditions, filterable, self-replicating L-bodies with virus-like size. Because filterability is one of the characteristics of L-forms, considerable interest has been shown in their capacity to cross the maternal-fetal barrier. The current study demonstrated isolation of mycobacterial L-form cultures from umbilical cord blood of 5 healthy newborns of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…In autistic children, fungal wall-free variants can be acquired from mothers by vertical pathway before birth and thus the newborn can be born already colonized with fungi. As was mentioned above, filterable L- forms are able to pass through the placental barrier and colonize the fetus 4,6 . In support of this assumption, were the demonstrated by TEM filterable forms in broth culture of an autistic child.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In autistic children, fungal wall-free variants can be acquired from mothers by vertical pathway before birth and thus the newborn can be born already colonized with fungi. As was mentioned above, filterable L- forms are able to pass through the placental barrier and colonize the fetus 4,6 . In support of this assumption, were the demonstrated by TEM filterable forms in broth culture of an autistic child.…”
Section: Discussionmentioning
confidence: 91%
“…The pregnancy may turn out a key milestone for entrance into embryo of mother’s bacterial and fungal L-forms. Recently, we reported that persisting in human blood filterable, self-replicating L-bodies with size of 100 nm are able to cross the maternal-fetal barrier, enter fetus blood circulation and colonize newborns 3,4,6 . It seems that mother’s dysbiotic blood microbiota can be acquired by embryo as early as during ontogenetic development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to determining the role of L-forms in the etiology of protracted and chronic infections in humans and animals, the current research efforts are aimed at studying the mechanisms of their resistance. Special attention is given to the L-bacteria circulating in the blood and also to the potentially dangerous uncontrolled colonization of morphologically atypical microbial cells (including those emerged after prophylactic vaccination) [39][40][41][42][43]. The very paradigm of the L-form existence calls into question the validity of the current concepts and some of the classical postulates of clinical microbiology [39][40][41]43].…”
Section: Reviewsmentioning
confidence: 99%
“…The supporting component of the CW specific for bacterial cells (except for Tenericutes and related mycoplasmas that naturally lack CW) is the biopolymer layer. In grampositive bacteria, this layer is thicker; it consists of peptidoglycan -a mesh of glycan threads and peptide bridges [40,44,45].…”
Section: Reviewsmentioning
confidence: 99%